2003
DOI: 10.1055/s-2003-38587
|View full text |Cite
|
Sign up to set email alerts
|

Why are guidelines not being followed?

Abstract: ÜbersichtenErstmalig wurden in Deutschland 1924 von F. Kraus medizinische Leitlinien in die gesundheitspolitische Diskussion eingebracht und in den "Leitsätzen für eine sparsame und doch sachgemäße Behandlungsweise der Kranken durch Ärzte" vom Reichsgesundheitsrat festgeschrieben (22). Bereits damals wird der medizinisch fachliche wie auch ökonomische Aspekt von Leitlinien deutlich. Im Laufe der letzten Jahre wurden hunderte Leitlinien zu verschiedenen Schwerpunktthemen von der Arbeitsgemeinschaft der wissensc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Nearly all specialists in the study reported high adherence to clinical guidelines – regardless of participation in the cardiology program. Even though implementation of guidelines can be difficult [14], high perceived adherence comes as no surprise: Guidelines are omnipresent in cardiology – in the past 3 years, the European Society of Cardiology alone published four to five new guidelines per year [15]. Though not legally binding in Germany, under certain circumstances guideline-adherence works as a defensive tool against accusations of malpractice [16, 17].…”
Section: Discussionmentioning
confidence: 99%
“…Nearly all specialists in the study reported high adherence to clinical guidelines – regardless of participation in the cardiology program. Even though implementation of guidelines can be difficult [14], high perceived adherence comes as no surprise: Guidelines are omnipresent in cardiology – in the past 3 years, the European Society of Cardiology alone published four to five new guidelines per year [15]. Though not legally binding in Germany, under certain circumstances guideline-adherence works as a defensive tool against accusations of malpractice [16, 17].…”
Section: Discussionmentioning
confidence: 99%